Ex-vivo lymphadenectomy during gastrectomy for adenocarcinoma optimizes lymph node yield - Afaneh, Cheguevara (J Gastrointest Surg, 2015)
INTRODUCTION: Variability in surgical and pathological techniques in Western centers may lead to inconsistency in lymph node staging in patients with gastric adenocarcinoma. We hypothesize that ex-vivo dissection (EVD) after gastrectomy for adenocarcinoma increases lymph node yield. METHODS: We retrospectively reviewed 222 consecutive patients who underwent gastrectomy with curative intent for adenocarcinoma between November 2010 and June 2014. In August of 2012, we began performing EVD of nodes in surgical specimens (EVD group, N=111), as opposed to submitting specimens en-bloc with lymph node basins attached to the specimen (No EVD group, N=111). Primary end-point was lymph node yield. RESULTS: The median number of lymph nodes procured was significantly higher in the EVD compared to the No EVD group (30 vs 21 lymph nodes, respectively; P<0.0001). Moreover, 28% of the No EVD group were not adequately staged (defined by ≤ 15 nodes), compared to 5% of the EVD group (P<0.0001). Stage-for-stage overall survival was not significantly different. CONCLUSION: EVD may be a useful tool to maximize lymph node yield. However, this had no impact on staging or survival. This is an interesting finding that warrants further investigation.